Digital Storytelling (DST) Media Development in Online Physics Learning Based on Computational Thinking - Kristian Dinata (SEAQIS Journal of Science Education, 2022)
The objectives of the study are: (1) producing learning media as a component of computational thinking learning; (2) describing the effectiveness of the thinking process based on DST media of online Physics learning; (3) describing user response based on computational thinking. The type of study is “Research and Development” by the ADDIE model. The data of the study were taken from: (1) the analysis of the data from students of X class in the period 2020/2021 and curriculum document of Physics material; (2) expert validation which are lecturers and Physics teachers of SMAN 2 South Bengkulu; and (3) test source from students of X class. There were 32 students of MIPA 4 (experiment class) and 33 students of MIPA 5 (control class). The methods of the study were observation, questionnaires, and tests. The analysis of the study was qualitative and quantitative method. The results of the study showed that: (1) expert validation was stated that some components of the learning process based on computational thinking such as syntax component, social system, principal reaction, support system, instructional effect, and accompaniment impact. Each of them is valid; (2) Based on the Quasi experiment, there was a significant difference between the learning outcomes using experiment test and control test (grade t count is 2.876 in other hand grade t table in 5% and grade p<0.005 is 2.042); (3) the students' responses from learning computational thinking were very positive (95%) and positive (5%). The conclusion is computational thinking learning is a valid product model, practice, effective, and suitable to be used.